1993
DOI: 10.1007/bf02374481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant human insulin-like growth factor I and insulin on counterregulation during acute plasma glucose decrements in normal and Type 2 (non-insulin-dependent) diabetic subjects

Abstract: Insulin-like growth factor I (65 micrograms/kg) or insulin (0.1 IU/kg) were injected i.v. on two separate occasions in random order in normal and in Type 2 (non-insulin-dependent) diabetic subjects. Insulin-like growth factor I and insulin injection resulted in identical decrements of plasma glucose concentrations after 30 min but in delayed recovery after insulin-like growth factor I as compared to insulin in both groups (p < 0.05 insulin-like growth factor I vs insulin). Counterregulatory increases in plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Specifically, in vitro studies have shown that IGF-I may have insulin-like effects in promoting the uptake of free fatty acids (FFA) into adipocytes, hepatocytes, and other tissues, and secondly, in promoting lipogenesis [83,122]. Consistent with this, several human studies [12,83,123,124], albeit, not all [11,33,72], reported that exogenous IGF-I administration significantly lowered serum FFA levels. In one typical study, for example, recombinant IGF-I administration reduced serum FFA levels from a mean of 411 ± 58 µM at baseline to just 165 ± 36 µM ( p < 0.001), with similar effects observed among patients with and without type 2 diabetes [83].…”
Section: The Igf-axis and Glucose And Lipid Metabolismmentioning
confidence: 92%
“…Specifically, in vitro studies have shown that IGF-I may have insulin-like effects in promoting the uptake of free fatty acids (FFA) into adipocytes, hepatocytes, and other tissues, and secondly, in promoting lipogenesis [83,122]. Consistent with this, several human studies [12,83,123,124], albeit, not all [11,33,72], reported that exogenous IGF-I administration significantly lowered serum FFA levels. In one typical study, for example, recombinant IGF-I administration reduced serum FFA levels from a mean of 411 ± 58 µM at baseline to just 165 ± 36 µM ( p < 0.001), with similar effects observed among patients with and without type 2 diabetes [83].…”
Section: The Igf-axis and Glucose And Lipid Metabolismmentioning
confidence: 92%
“…This hypothesis has been corroborated by clinical trials showing that administration of recombinant human (rh)-IGF-I improves insulin sensitivity and hyperglycemia in patients suffering from type 1 diabetes mellitus (T1DM), type 2 diabetes mellitus (T2DM) as well as severe insulin resistance [18][19][20][21]. However, the possible role of endogenous IGF-I in glucose homeostasis remains to be clarified.…”
Section: Introductionmentioning
confidence: 87%
“…IGF-I treatment lowers plasma glucose in healthy subjects, in patients with T1DM and T2DM and even in patients suffering from severe insulin resistance due to mutations in the insulin receptor (IR) gene (type A diabetes) [18][19][20]217,218]. The glucose lowering effect of IGF-I is mediated through an increased peripheral glucose uptake and glycogen synthesis in skeletal muscles, as well as a suppression of the hepatic glucose production (HGP).…”
Section: Effect Of Igf-i On Glucose Homeostasismentioning
confidence: 99%
“…The acute effects of IGF-I on peripheral and hepatic glucose metabolism in type 2 diabetic humans have been less well characterized. Laagerand and Keller (26) demonstrated that the decline in plasma glucose concentration in response to intravenous IGF-I was impaired in type 2 diabetic individuals, but this study did not examine whether the IGF-I resistance was present in skeletal muscle, in liver, or in both. In a previous study (7), we demonstrated that chronic subcutaneous IGF-I administration in type 2 diabetic patients inhibited EGP, reduced the fasting glucose concentration, and produced a small increase in insulin-mediated glucose disposal.…”
mentioning
confidence: 94%